A programme of research to set priorities and reduce uncertainties for the prevention and treatment of skin disease - Kim S Thomas; Jonathan M Batchelor; Fiona Bath-Hextall; Joanne R Chalmers; Tessa Clarke; Sally Crowe; Finola M Delamere; Viktoria Eleftheriadou; Nicholas Evans; Lester Firkins; Nicola Greenlaw; Louise Lansbury; et al. (NIHR Journals Library, 2016)
Background: Skin diseases are very common and can have a large impact on the quality of life of patients and caregivers. This programme addressed four diseases: (1) eczema, (2) vitiligo, (3) squamous cell skin cancer (SCC) and (4) pyoderma gangrenosum (PG). Objective: To set priorities and reduce uncertainties for the treatment and prevention of skin disease in our four chosen diseases. Design: Mixed methods including eight systematic reviews, three prioritisation exercises, two pilot randomised controlled trials (RCTs), three feasibility studies, two core outcome initiatives, four funding proposals for national RCTs and one completed national RCT. Setting: Secondary care, primary care and the general population. Participants: Patients (and their caregivers) with eczema, vitiligo, SCC and PG, plus health-care professionals with an interest in skin disease. Interventions: Our three intervention studies included (1) barrier enhancement using emollients from birth to prevent eczema (pilot RCT); (2) handheld narrowband ultraviolet light B therapy for treating vitiligo (pilot RCT); and (3) oral ciclosporin (Neoral®, Novartis Pharmaceuticals) compared with oral prednisolone for managing PG (pragmatic national RCT). Results: Systematic reviews included two overarching systematic reviews of RCTs of treatments for eczema and vitiligo, an umbrella review of systematic reviews of interventions for the prevention of eczema, two reviews of treatments for SCC (one included RCTs and the second included observational studies), and three reviews of outcome measures and outcome reporting. Three prioritisation partnership exercises identified 26 priority areas for future research in eczema, vitiligo and SCC. Two international consensus initiatives identified four core domains for future eczema trials and seven core domains for vitiligo trials. Two pilot RCTs and three feasibility studies critically informed development of four trial proposals for external funding, three of which are now funded and one is pending consideration by funders. Our pragmatic RCT tested the two commonly used systemic treatments for PG (prednisolone vs. ciclosporin) and found no difference in their clinical effectiveness or cost-effectiveness. Both drugs showed limited benefit. Only half of the participants' ulcers had healed by 6 months. For those with healed ulcers, recurrence was common (30%). Different side effect profiles were noted for each drug, which can inform clinical decisions on an individual patient basis. Three researchers were trained to PhD level and a dermatology patient panel was established to ensure patient involvement in all aspects of the programme. Conclusions: Findings from this programme of work have already informed clinical guidelines and patient information resources. Feasibility studies have ensured that large national pragmatic trials will now be conducted on important areas of treatment uncertainty that address the needs of patients and the NHS. There is scope for considerable improvement in terms of trial design, conduct and reporting for RCTs of skin disease, which can be improved through wider collaboration, registration of trial protocols and complete reporting and international consensus over core outcome sets. Three national trials have now been funded as a result of this work. Two international initiatives to establish how best to measure the core outcome domains for eczema and vitiligo are ongoing. Trial registration: Current Controlled Trials Barrier Enhancement for Eczema Prevention (BEEP) (ISRCTN84854178 and NCT01142999), Study of Treatments fOr Pyoderma GAngrenosum Patients (STOP GAP) (ISRCTN35898459) and Hand Held NB-UVB for Early or Focal Vitiligo at Home (HI-Light Pilot Trial) (NCT01478945). Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 4, No. 18. See the NIHR Journals Library website for further project information.